Biotechnological metabolization system has the potential to improve the predictive ability of the fish embryo acute toxicity (FET) test with the zebrafish (Danio rerio) - Reichstein, Inska; Becker, Alischa H.; Johann, Sarah; Braunbeck, Thomas; Schiwy, Sabrina; Hollert, Henner; Schiwy, Andreas (Environmental sciences Europe, 2024)
The fish embryo acute toxicity (FET) test with the zebrafish (Danio rerio) was developed to assess the acute fish toxicity of chemicals or environmental samples as a replacement for the Acute Fish Test (AFT) with juvenile fish. However, the FET is not yet established in the regulatory context. One reason is the (postulated) difference between the biotransformation capacities of embryos and juvenile fish.
Gesehen am 06.09.2024